Feature extraction using indicators of cyclostationarity for a mechanical diagnosis purpose - Raad, Amani; Antoni, Jérôme; Sidahmed, Ménad (Computer Assisted Methods in Engineering and Science, 2005)
This paper focuses on features extraction based on cyclostationarity for diagnosis purpose. The objective is to derive new indicators for the diagnosis of rotating machinery. These indicators are based on cyclic higher order statistics and generalize some existing ones for the second order statistics. A comprehensive methodology is proposed for obtaining a diagnosis objective; a crucial example is presented, relating to vibration signals of a gearbox. Results demonstrate the effectiveness of these features to detect spalling in gearbox.